Therapeutic Effects in a Transient Middle Cerebral Artery Occlusion Rat Model by Nose-To-Brain Delivery of Anti-TNF-Alpha siRNA with Cell-Penetrating Peptide-Modified Polymer Micelles - Takanori Kanazawa; Takumi Kurano; Hisako Ibaraki; Yuuki Takashima; Toyofumi Suzuki; Yasuo Seta (MDPI AG, 2019)
We previously reported that siRNA delivery to the brain is improved by the nose-to-brain delivery route and by conjugation with polyethylene glycol-polycaprolactone (PEG-PCL) polymer micelles and the cell-penetrating peptide, Tat (PEG-PCL-Tat). In this study, we evaluated the nose-to-brain delivery of siRNA targeting TNF-α (siTNF-α) conjugated with PEG-PCL-Tat to investigate its therapeutic effects on a transient middle cerebral artery occlusion (t-MCAO) rat model of cerebral ischemia-reperfusion injury. Intranasal treatment was provided 30 min after infarction induced via suturing. Two hours after infarction induction, the suture was removed, and blood flow was released. At 22 h post-reperfusion, we assessed the infarcted area, TNF-α production, and neurological score to determine the therapeutic effects. The infarcted area was observed over a wide range in the untreated group, whereas shrinkage of the infarcted area was observed in rats subjected to intranasal administration of siTNF-α with PEG-PCL-Tat micelles. Moreover, TNF-α production and neurological score in rats treated by intranasal administration of siTNF-α with PEG-PCL-Tat micelles were significantly lower than those in untreated and naked siTNF-α-treated rats. These results indicate that nose-to-brain delivery of siTNF-α conjugated with PEG-PCL-Tat micelles alleviated the symptoms of cerebral ischemia-reperfusion injury.